2010 4th International Conference on Multimedia and Ubiquitous Engineering 2010
DOI: 10.1109/mue.2010.5575094
|View full text |Cite
|
Sign up to set email alerts
|

Stream-Based XML Template Compression for Wireless Sensor Network Data Management

Abstract: Using structured data formats like XML in wireless sensor networks to support exchangeability and heterogeneity on application level has become an important research topic in the area of large scale networked sensing systems. Besides, the usage of XML encourages the adaptation of service oriented programming techniques to simplify sensor network application engineering. While the sensor nodes still have significant resource limitations in terms of energy and memory capacity and computational power, recent data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A further advantage of the XOBE SN precompiler is the compression of embedded XML data, which we explain in the following paragraphs. This paper extends the contributions of [16][17] by reformulating queries according to the compressed datastructure of the embedded XML data, such that the query is much faster evaluated by a more direct navigation to its result. The query reformulation and evaluation is explained in more detail in the next chapter.…”
Section: Xobementioning
confidence: 86%
See 2 more Smart Citations
“…A further advantage of the XOBE SN precompiler is the compression of embedded XML data, which we explain in the following paragraphs. This paper extends the contributions of [16][17] by reformulating queries according to the compressed datastructure of the embedded XML data, such that the query is much faster evaluated by a more direct navigation to its result. The query reformulation and evaluation is explained in more detail in the next chapter.…”
Section: Xobementioning
confidence: 86%
“…No contribution to embedded languages discusses compression techniques except those for XOBE [16][17]. [17] is an embedded language for XML data and queries.…”
Section: Related Work Of Embedded Languagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoeller et al [15,16,17] identified the inefficient management of XML formatted data in resource-constrained devices as a barrier to overcome in order to achieve full interoperability. They defined a series of mechanisms to efficiently manage XML in terms of processing, storing and transmission.…”
Section: Related Workmentioning
confidence: 99%
“…Sensor node hardware restictions have been addressed using an XPath engine on updateable compressed XML data, reducing memory and energy consumption [24]. Furthermore, this work has been extended to support larger sets of data within the sensor network using stream-oriented XML compression in order to have a dynamic queriable system [25]. This research is motivated by the necessity to improve network management over a wireless embedded internet, however, it can be extended to general networks.…”
Section: Related Workmentioning
confidence: 99%